Comparative Proteomic Analysis Provides New Insights Into Low Nitrogen-Promoted Primary Root Growth in Hexaploid Wheat - Xu, Yanhua; Ren, Yongzhe; Li, Jingjing; Li, Le; Chen, Shulin; Wang, Zhiqiang; Xin, Zeyu; Chen, Feng; Lin, Tongbao; Cui, Dangqun; Tong, Yiping (Frontiers in Plant Science, 2019)
Nitrogen deficient environments can promote wheat primary root growth (PRG) that allows for nitrogen uptake in deep soil. However, the mechanisms of low nitrogen-promoted root growth remain largely unknown. Here, an integrated comparative proteome study using iTRAQ analysis on the roots of two varieties and their descendants with contrasting response to low nitrogen (LN) stress was performed under control (CK) and LN conditions. In total, 84 differentially abundant proteins (DAPs) specifically involved in the process of LN-promoted PRG were identified and 11 pathways were significantly enriched. The Glutathione metabolism, endocytosis, lipid metabolism and phenylpropanoid biosynthesis pathways may play crucial roles in the regulation of LN-promoted PRG. We also identified 59 DAPs involved in the common response to LN stress in different genetic backgrounds. The common responsive DAPs to LN stress were mainly involved in nitrogen uptake, transportation and remobilization, and LN stress tolerance. Taken together, our results provide new insights into the metabolic and molecular changes taking place in contrasting varieties under LN conditions, which provide useful information for the genetic improvement of wheat root traits and nitrogen use efficiency in wheat.